A Prospective Study of Suicidal Ideation in Posttraumatic Stress Disorder: The Role of Perceptions of Defeat and Entrapment. Issue 1 (9th June 2014) - Panagioti, Maria; Gooding, Patricia A.; Tarrier, Nicholas
<x xml:space="preserve">Abstract</x> Objectives This study aimed to provide the first prospective test of the ability of defeat and entrapment to predict suicidal ideation in posttraumatic stress disorder (PTSD) after controlling for the effects of PTSD severity, comorbid depressive symptoms, and hopelessness on suicidal ideation. Methods Participants were 52 individuals diagnosed with PTSD. Baseline and follow‐up assessments were 13 to 15 months apart. Defeat and entrapment were conceptualized and analyzed as a unique construct (defeat/entrapment) in this study. Multiple regression analysis was applied to examine the predictive effects of defeat/entrapment on suicidal ideation. Results Defeat/entrapment scores predicted changes in the levels of suicidal ideation at follow‐up while controlling for baseline suicidal ideation, PTSD severity, comorbid depressive symptoms, and hopelessness. Conclusions These outcomes provide support to contemporary models of suicidality that suggest that defeat/entrapment is a strong predictor of suicidality in PTSD.